Bioactive Saussurea costus PCL–Gelatin Nanofibers: A Novel Nanoplatform for Enhanced Wound Healing - Lababidi, Jude Majed (AUC Knowledge Fountain, 2026)
Wound healing proceeds through coordinated phases of inflammation, tissue formation, and remodeling, and therefore benefits from dressings that can simultaneously control infection, modulate inflammation, and support regeneration. Saussurea costus (Sc) is documented to possess anti-inflammatory and antibacterial activities, motivating its incorporation into advanced biomaterial platforms for cutaneous repair. Here, we engineered electrospun poly(ε- caprolactone)–gelatin nanofibers containing 6% Sc extract (6% Sc-loaded PCL–GL) and evaluated their physicochemical attributes, release behavior, and therapeutic performance in vitro and in vivo. Process optimization yielded bead-free, nanoscale fibers whose mean diameter increased upon Sc loading, as confirmed by scanning electron microscopy (SEM), indicating viscosity- driven thickening consistent with extract incorporation. Fourier transform infrared (FTIR) spectroscopy verified characteristic functional groups and polymer–extract interactions, while X- ray diffraction (XRD) showed preservation of PCL crystallinity within the composite scaffold. Thermogravimetric analysis (TGA) demonstrated a stable degradation profile appropriate for handling and storage, and uniaxial tensile testing established a durable mechanical window compatible with wound-dressing use. Static contact-angle measurements evidenced a marked increase in surface hydrophilicity with Sc exhibiting contact angle of 54.5° ± 2.04 vs. 110° ± 0.02 for unloaded nanofibers. Ultraviolet–visible spectrophotometry revealed a controlled, sustained release profile of Sc over one week, supporting prolonged local bioactivity without burst- exhaustion. Antibacterial assessments against clinically relevant wound pathogens, Pseudomonas aeruginosa, Staphylococcus aureus, and Escherichia coli, demonstrated potent dose-responsive killing, with the 6% Sc formulation achieving 7-log reductions relative to controls. Cytocompatibility testing on human skin fibroblasts showed no significant loss of viability after direct contact with 6% Sc-loaded PCL–GL , indicating material safety for cellular interfaces. In a rat full-thickness excisional model, daily application of 6% Sc-loaded PCL–GL accelerated wound healing showing 83.21 ± 4.95% wound closure in the treated group compared with 67.88 ± 7.38% in untreated group. Gene-expression analysis at day 14 revealed significant downregulation of interleukin-6 (IL-6) together with upregulation of BAX and matrix metalloproteinase-3 (MMP-3), implicating tempered inflammation, orderly apoptotic clearance of damaged cells, and active matrix remodeling/angiogenesis. Immunohistochemistry aligned with the transcriptional data, showing moderate vascular endothelial growth factor (VEGF) and transforming growth factor-β1 (TGF-β1) expression and robust BAX staining in treated wounds, consistent with vascular 4 maturation and controlled tissue turnover. Systemic safety was supported by normal histoarchitecture in immune organs, and no adverse weight or behavioral effects were observed during the study period. These findings position 6% Sc-loaded PCL–GL nanofibers as a promising, mechanism-informed dressing that unites barrier protection, antibacterial and antioxidant functions, and pro-healing signaling into a single, biocompatible platform. Future work should refine composition and fiber architecture of individual Sc constituents to validate efficacy in chronic and infected wound models and larger animals, and advance translation through scalable manufacturing, sterilization/stability qualification, and early clinical evaluation.